A Constitutive Equation for the Flow and Densification Behaviors of Powder Metallurgy Fe–0.5C–2Cu Steel at Elevated Temperatures. Issue 4 (4th October 2016) - Guo, Biao; Ao, Jinqing; Xu, Yi; Meng, Zhongwei
Abstract : The flow and densification behaviors of powder metallurgy (PM) Fe–0.5C–2Cu (wt%) steel are investigated by conducting isothermal hot compression tests on a Gleeble 3800 thermo‐simulator in the temperature range of 850–1000 °C, a strain rate of 0.01–10 s −1, and a compressibility of 35–65%. It is found that the true stress–strain curves obtained from the hot compression tests demonstrated the characteristics typical of persistent hardening as the gradual decrease of the stress rise. The experimental results show that the flow and densification behaviors of the PM steel are greatly affected by the deformation temperature, strain rate, and deformation amount. A constitutive equation that predicts the dynamic flow stress and relative density in hot compression of the PM steel is established. The predicted values of flow stress and relative density are in good agreement with the experimental results, which demonstrate that the proposed constitutive equation is able to well characterize the flow and densification behaviors of the PM steel at elevated temperatures. The present study can provide important and basic data for the finite element simulation of plastic working processes of the PM steel. Abstract : The flow and densification behaviors of PM Fe–0.5C–2Cu steel are investigated by hot compression tests . The flow and densification behaviors are greatly affected by the hot deformation parameters. A constitutive equation is proposed to characterize the flow and densification behaviors. The proposed constitutive equation has good prediction accuracy in dynamic flow stress and relative density.